EXPERIMENTAL INSTALLATION FOR DETERMINATION OF AERODYNAMIC CHARACTERIS-TICS OF WIG - Українець, Е. О.; Спіркін, Є. В.; Кудрявцев, В. Г.; Клочков, Ю. П.; Нечитайло, В. І. (Science-based technologies, 2019)
The problem of increasing the speed of ships to achieve tactical advantages is one of the key issues in the development of the Naval Forces. The purpose of the article is to justify the possibility of creating a rotary unit for determining the basic aerodynamic characteristics of screenplanes, developing a method for conducting a model experiment on a rotary installation. As an object of experimental aerodynamic research in the wind tunnel T-1, a model of the WIG of the type “Орленок” and, the shielding surface which was a wooden smooth screen were chosen. As a result of processing the experimental data for the WIG model, the dependences of the lift coefficients on the angle of attack were obtained. It is shown that the determination of the aerodynamic characteristics of WIG in wind tunnels requires large power capacities, high qualifications of the researcher, and the methods of conducting a model experiment with shielding surfaces have a number of limitations. It was concluded that reducing the cost of a model experiment can be achieved using a rotative unit, while the simplicity of the implementation of a wave screen in such a setup is a significant advantage over a model experiment in a wind tunnel. The variants of the rotative installation for the study of the main aerodynamic characteristics of the WIG are feasible. In this case, the known scheme of the rotative installation is changed, since the screening surface itself plays the role of a screen to reduce the effect of a slipstream. In the subsequent work it is supposed to substantiate the main technical characteristics of the rotational installation, the development of the methodology of conducting the experiment.